2013
DOI: 10.1111/maps.12244
|View full text |Cite
|
Sign up to set email alerts
|

Neutron absorption constraints on the composition of 4 Vesta

Abstract: Abstract-Global maps of the macroscopic thermal neutron absorption cross section of Vesta's regolith by the Gamma Ray and Neutron Detector (GRaND) on board the NASA Dawn spacecraft provide constraints on the abundance and distribution of Fe, Ca, Al, Mg, and other rock-forming elements. From a circular, polar low-altitude mapping orbit, GRaND sampled the regolith to decimeter depths with a spatial resolution of about 300 km. At this spatial scale, the variation in neutron absorption is about seven times lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 102 publications
14
83
0
Order By: Relevance
“…Application of crater statistical techniques were applied to mapped terrains to determine relative and absolute model ages of portions of the surface (Marchi et al, 2012a(Marchi et al, , 2012bO'Brien et al, 2014;Schmedemann et al, 2014). Hyperspectral and thermophysical analyses of multi-wavelength visible and near-infrared data from Dawn's Visible and Infrared Spectrometer (VIR: De Sanctis et al, 2012;Ammannito et al, 2013a), and correlation of geology with geochemical distributions derived from Dawn's Gamma Ray and Neutron Detector (GRaND: Prettyman et al, 2012Prettyman et al, , 2013Yamashita et al, 2013), were used to provide information on the mineralogical and physical composition of surface materials. Finally, assessment of Vesta's gravity, mass distributions, and crustal thickness were obtained from Dawn's Radio Science experiment (Konopliv et al, 2013;Park et al, 2014;Raymond et al, 2013Raymond et al, , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Application of crater statistical techniques were applied to mapped terrains to determine relative and absolute model ages of portions of the surface (Marchi et al, 2012a(Marchi et al, , 2012bO'Brien et al, 2014;Schmedemann et al, 2014). Hyperspectral and thermophysical analyses of multi-wavelength visible and near-infrared data from Dawn's Visible and Infrared Spectrometer (VIR: De Sanctis et al, 2012;Ammannito et al, 2013a), and correlation of geology with geochemical distributions derived from Dawn's Gamma Ray and Neutron Detector (GRaND: Prettyman et al, 2012Prettyman et al, , 2013Yamashita et al, 2013), were used to provide information on the mineralogical and physical composition of surface materials. Finally, assessment of Vesta's gravity, mass distributions, and crustal thickness were obtained from Dawn's Radio Science experiment (Konopliv et al, 2013;Park et al, 2014;Raymond et al, 2013Raymond et al, , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…This lobe has a low iron counting rate and possesses almost the same spatial distribution as the region found in FC images. Another comparison between GRaND and FC data is given by Prettyman et al (2013), where a diogenite rich region with low Percentage of Eucritic Material (POEM) has been found by GRaND in nearly the same area.…”
Section: Rheasilvia Ejectamentioning
confidence: 99%
“…Those data were presented and discussed in Yamashita et al (2013b), and the data shown in this work were taken from the NASA Planetary Data Systems (PDS) . Vestan thermal neutron absorption data presented here also are from the NASA PDS (Prettyman, 2013), and were first presented and discussed in Prettyman et al (2013). Fe concentrations and thermal neutron macroscopic absorption for cross sections for HEDs are part of a As can be seen in Fig. 14, basaltic eucrite, cumulate eucrite and orthopyroxenitic diogenites (the three main vestan igneous lithologies, as per the HEDs) establish three distinct regions in Fe vs. eff -space.…”
Section: Hed Compositions On the Surfacementioning
confidence: 95%
“…Surprisingly, reflectance, gamma ray and neutron spectral data thus far show no signs of olivine in the Rheasilvia basin Prettyman et al, 2013;Ammannito et al, 2013a). Given the size of the Rheasilvia basin, it was anticipated that the mantle of Vesta would be exposed, likely including olivine-rich materials.…”
Section: Observations From Fc Images and Vir Spectra: One Big Howarditementioning
confidence: 95%
See 1 more Smart Citation